Low Prevalence of Antibody to Hepatitis G Virus Among the Risk Groups and Healthy Population of Bangladesh (Bangladesh Journal of Medical Microbiology, 2012)
Hepatitis G virus (HGV) is a RNA virus, which was identified in 1995-1996 as a transfusion transmissible virus and is associated with acute or chronic hepatitis. The sero-prevalence of hepatitis G virus was evaluated among various risk groups and healthy controls from Bangladesh.A total of 252 subjects comprising of Intra-venous drug users (n-40), commercial sex workers (n-30), multiply transfused patients (n-62), hemodialysis patients (n-30), anti HCV positive patients (n-30), anti HIV positive patients (n-30) and healthy population (n-30) were included in this study. Antibody to hepatitis G virus E-2 protein was detected in the serum by Enzyme linked immunosorbent assay (ELISA). The overall antibody prevalence of HGV was 3.2%. The highest prevalence (10%) was observed among commercial sex workers, followed by intra-venous drug users (5%). The lowest prevalence (3.3%) was observed among each of the groups of hemodialysis patients, anti-HCV positive patients and anti-HIV positive patients. Anti-HGV antibody was not detected among any subjects from the control group. Epidemiologic data indicate that HGV is prevalent in risk groups though at very low prevalence.DOI: http://dx.doi.org/10.3329/bjmm.v4i2.10822